Analisis Peran Norma Hukum Dalam Mempertahankan Kestabilan Negara (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
This research is entitled " Analysis of the Role of Legal Norms in Defending State Stability" This research was carried out with the aim of finding out the actual role of legal norms in maintaining state stability. The method used in this research is a qualitative approach literature study research method. This research is useful for developing scientific insight into norms as a means of assessing the operation of law in society and the role of legal norms in maintaining state stability.